Comunicación multimedia y el rol de los periodistas deportivos radiales, en la ciudad de Quevedo, año 2019 - Miranda Muñoz, Javier Enrique (2020)
This research project was developed based on the problems evidenced in the Quevedo canton, Province of Los Ríos, regarding the role of sports journalists and multimedia communication, for which the respective objectives framed and supported with the due research and data collection for decision-making focused on solving all the problems found. In Chapter 1, the topic of research based on international, national, local and institutional contexts will be developed, raising the respective problematic situation, and in the same way the respective justification for setting the objectives to be achieved. Chapter 2, will contain the necessary theoretical support in the conceptual framework, referential and research background attached to the subject under investigation, supported by reference of the most representative authors, all this research assembly to conclude with the hypotheses of the case. In Chapter 3, the results obtained from data collection, subsequent representation with the respective statistical tables and graphic representation will be announced. The respective proposal will be developed in Chapter 4, outlining the objectives that need to be achieved as part of the structure of the proposed alternative to solve the case, in addition the respective conclusions and recommendations regarding the use of multimedia communication will be defined part of sports journalists, to improve their professional performance.